Dehydrated alfalfa vs. Vitamin A with and without Aureomycin to cattle rations using sorghum grain - Richardson, D.; Smith, E.F.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
The animals’ in this test were used in a previous wintering test to study grain vs. forage type sorghum silage; dehydrated alfalfa as a source of Vitamin A vs. Vitamin A; and Vitamin A with and without Aureomycin. At the end of the test, cracked sorghum grain was added to the ration and the fattening phase was started. Animals that had received dehydrated alfalfa in the wintering phase continued to receive it during the fattening phase and likewise those that received Vitamin A continued to receive Vitamin A. The dehydrated alfalfa contained approximately 50 mgs. of carotene per pound. Assuming 400 I.U. of Vitamin A per milligram of carotene, one half pound of dehydrated alfalfa supplied the equivalent of 10,000 I.U. of Vitamin A; hence, the comparison of one half pound dehydrated alfalfa pellots as a source of Vitmain A with 10,000 I.U. of preformed Vitamin A. each source of Vitamin A was fed with and without Aureomycin. The ration ingredients and average daily consumption are shown in Table 1. Salt and a mixture of salt and dicalcium phosphate were fed free choice.
Keywords: Beef; Dehydrated alfalfa vs. Vitamin A; Sorghum grain